Choledochal Cyst: Case Variations and Management - Girsang, Andrew Deardo Purba; Fattahillah T, Rizqy Agung; Nazilinly, Fitri; Kamilah, Nilam Nurmilatun; Pramudya, I Nengah Andra Putra; Mario, Andina Nabilah; Faqih, Fauzan; Zuhan, Arif (Jurnal Biologi Tropis, 2024)
Choledochal Cyst (CC) is a congenital anomaly characterized by the dilation of intrahepatic and/or extrahepatic bile ducts. This condition can occur at any age but is more common in infants and children, accounting for 80% of cases. This study aims to evaluate the clinical characteristics, diagnostic approaches, and optimal management options for choledochal cysts, accompanied by case variations. The method used in this study is a literature review, gathering relevant literature from various references focused on the topic of choledochal cysts. Literature searches were conducted using library search websites, including PubMed, ScienceDirect, Cochrane Library, Google Scholar, and ProQuest, with the search keyword "Choledochal Cyst." The review indicates that choledochal cysts are more common in females and people of Asian descent, especially in Japan, with the most common symptoms presenting as the classic triad of abdominal pain, jaundice, and a palpable mass in the right upper quadrant of the abdomen. This condition is more frequently diagnosed in children than in adults. Further research is needed to explore definite preventive efforts regarding this disease, as it is rare and its etiology remains uncertain.